Shake, rattle, and roll : the world's most amazing volcanoes, earthquakes, and other forces - Christian, Spencer; Blashko, Abe; Felix, Antonia; Wolk-Stanley, Jessica (New York : J. Wiley & Sons, 1997)
Examines the powerful forces found in the Earth, with an emphasis on earthquakes and volcanoes.
Includes index.
Appraisal-Science Books for Young People
Science and Children (N.S.T.A.)
Wilson's Junior High School
6.7
3-6
Keywords: Earthquakes -- Juvenile literature; Volcanoes -- Juvenile literature; Earthquakes; Volcanoes; Earthquakes; Volcanoes